Path to greener business pastures - New Straits Times, Samantha Joseph (2012)
A Master's in Business Administration is one of the most common, if not the most common postgraduate qualification at the moment. This can be attributed to its broad application and all-inclusive nature, as graduates have come from backgrounds as varied as agriculture and microbiology and graduated into positions ranging from self-made entrepreneur to directors.